Visualization of Synchronous or Asynchronous Release of Single Synaptic Vesicle in Active-Zone-Like Membrane Formed on Neuroligin-Coated Glass Surface - Funahashi, Junichiro; Tanaka, Hiromitsu; Hirano, Tomoo (Frontiers in Cellular Neuroscience, 2018)
Fast repetitive synaptic transmission depends on efficient exocytosis and retrieval of synaptic vesicles around a presynaptic active zone. However, the functional organization of an active zone and regulatory mechanisms of exocytosis, endocytosis and reconstruction of release-competent synaptic vesicles have not been fully elucidated. By developing a novel visualization method, we attempted to identify the location of exocytosis of a single synaptic vesicle within an active zone and examined movement of synaptic vesicle protein synaptophysin (Syp) after exocytosis. Using cultured hippocampal neurons, we induced formation of active-zone-like membranes (AZLMs) directly adjacent and parallel to a glass surface coated with neuroligin, and imaged Syp fused to super-ecliptic pHluorin (Syp-SEP) after its translocation to the plasma membrane from a synaptic vesicle using total internal reflection fluorescence microscopy. An AZLM showed characteristic molecular and functional properties of a presynaptic active zone. It contained active zone proteins, CAST, Bassoon, Piccolo, Munc13 and RIM, and showed an increase in intracellular Ca2+ concentration upon electrical stimulation. In addition, single-pulse stimulation sometimes induced a transient increase of Syp-SEP signal followed by lateral spread in an AZLM, which was considered to reflect an exocytosis event of a single synaptic vesicle. The diffusion coefficient of Syp-SEP on the presynaptic plasma membrane after the membrane fusion was estimated to be 0.17 – 0.19 m2/sec, suggesting that Syp-SEP diffused without significant obstruction. Synchronous exocytosis just after the electrical stimulation tended to occur at multiple restricted sites within an AZLM, whereas locations of asynchronous release occurring later after the stimulation tended to be more scattered. more.